Stability of antioxidant activity leaf extract of Guadua angustifolia Kunth - Inga Santillán, Charles A. (2020)
Bamboo ( Guadua angustifolia Kunth) is a promising species of the tropics with great industrial potential, since all parts of the plant can be used. In addition to cane, leaves are a very important source of antioxidants. The objective of the investigation was to evaluate the stability of the antioxidant capacity of the leaf extract G. angustifolia during storage. For this, a complete 2A x 2B factorial design was executed, with three replicas, where A= type of container (transparent and amber glass container) and B = storage temperature (ambient temperature and 4th refrigeration). The antioxidant activity was measured as a response variable, measured in percent inhibition, using the DPPH technique, every three days for a month. Finding that the extract ofthe bamboo leaves was very stable, after 30 days 80% of antioxidant activity was found and can be stored at room temperature and in transparent containers without altering its antioxidant capacity.